New Vocabularies of May Fourth Studies - Lin, Carlos Yu-Kai; Mair, Victor H. (Asian Studies E-Books Online, Collection 2025, 2025)
Why did the "Shandong Question" vanish in the May Fourth narrative? How did conservatives and traditionalists endure admist the progressive wave of the new culture movement? What role did Confucian ritualism and religion play in shaping May Fourth literature? Is an uncanny connection hidden between "Return Qingdao" and "Liberate Hong Kong"? This volume, edited by Carlos Yu-Kai Lin and Victor H. Mair, and with contributors from across the fields of intellectual history, literature and languages, philosophy, and Asian studies, answers these questions and offers new insights into the May Fourth movement. It explores this pivotal historical event both as a singular occurrence and as a sustaining cultural-intellectual campaign. The new volume is brimming with fresh perspectives, uncovering these enigmas, and unveiling the nuanced and intricate world of the May Fourth to its discening readers.